Application of UAV-SfM Photogrammetry to Monitor Deformations of Coastal Defense Structures - Santiago García-López; Mercedes Vélez-Nicolás; Verónica Ruiz-Ortiz; Pedro Zarandona-Palacio; Antonio Contreras-de-Villar; Francisco Contreras-de-Villar; Juan José Muñoz-Pérez (Remote Sensing)
Coastal defense has traditionally relied on hard infrastructures like breakwaters, dykes, and groins to protect harbors, settlements, and beaches from the impacts of longshore drift and storm waves. The prolonged exposure to wave erosion and dynamic loads of different nature can result in damage, deformation, and eventual failure of these infrastructures, entailing severe economic and environmental losses. Periodic post-construction monitoring is crucial to identify shape changes, ensure the structure’s stability, and implement maintenance works as required. This paper evaluates the performance and quality of the restitution products obtained from the application of UAV photogrammetry to the longest breakwater in the province of Cádiz, southern Spain. The photogrammetric outputs, an orthomosaic and a Digital Surface Model (DSM), were validated with in situ RTK-GPS measurements, displaying excellent planimetric accuracy (RMSE 0.043 m and 0.023 m in X and Y, respectively) and adequate altimetric accuracy (0.100 m in Z). In addition, the average enveloping surface inferred from the DSM allowed quantification of the deformation of the breakwater and defining of the deformation mechanisms. UAV photogrammetry has proved to be a suitable and efficient technique to complement traditional monitoring surveys and to provide insights into the deformation mechanisms of coastal structures.